From Crisis To Strategy: Mainstreaming Climate Risk In Health Systems Planning. - Sorensen, Cecilia; Borghi, Josephine; Bauhoff, Sebastian (Health Affairs, 2026)
Climate change poses a growing threat to health care systems worldwide, exposing weaknesses in infrastructure, workforce, and governance. Climate risk--defined by the interaction of hazard, exposure, and vulnerability--is both similar to and distinct from other systemic risks that health care systems must manage. We propose a risk-based framework that integrates insights from disaster risk management and health systems thinking to identify adaptation strategies. Our approach emphasizes understanding and addressing the upstream determinants of climate risk, including the intersectoral operating environment and social and environmental vulnerabilities that amplify health impacts. This perspective links climate risk reduction to the broader agenda of health equity.Within the health sector, climate change exerts simultaneous pressure on both demand and supply, challenging systems to move from reactive crisis response toward proactive, risk-informed planning. Established tools--such as strategic investment, workforce planning, and emergency preparedness--can be leveraged to manage climate-related risks while advancing core health policy goals. Framing climate change as a systemic risk encourages the integration of climate considerations into everyday policy and planning and strengthens health care system performance.